A retrospective study on the correction of distal arthrogryposis with a progressive extension brace - Zhou, Jiateng; Zhang, Tong; Wang, Zhibo; Li, Dongdong; Wu, Xin; Yu, Qinyuan; Wang, Bin (Frontiers in Pediatrics, 2024)
Purpose Camptodactyly, clasped thumbs, and windblown hands are distinctive features of distal arthrogryposis (DA). Current therapeutic interventions often yield suboptimal effects, predisposing patients to relapses and complications. This study explicates a corrective approach involving a progressive extension brace for the management of DA and evaluates its clinical outcomes. Methods Between 2015 and 2023, progressive extension braces were used in 32 DA patients, with an average follow-up of 4.8 years. Patients were stratified by age into four groups: 0–1, 1–3, 3–7, and above 7 years. The correction of camptodactyly was assessed based on the total active movement (TAM) of metacarpophalangeal joints (MPJ) and proximal interphalangeal joints (PIPJ), as well as the extensor lag of PIPJ. Clasped thumb correction was evaluated by measuring the thumb-to-index finger metacarpal angle (M1M2 angle) and the degree of deviation at the first MPJ (M1P1 angle). The quality of life for the children was measured using PedsQL 4.0, while parental satisfaction was gauged using the FACE questionnaire. Results Earlier intervention with a progressive extension brace yielded superior corrective results. Infants aged 0–1 year and toddlers aged 1–3 years achieved average TAM scores of 152° and 126° after correction; however, patients older than 3 years experienced a significant decrease in TAM with the same treatment. Infants and toddlers with DA showed improvement in the average extensor lag from 46° to 6°. The M1M2 angle increased from an average of 38° to 65°, with the M1P1 angle decreasing from an average of 43° to 5°. After the treatment, average PedsQL scores of 94.7 (parent-reported) and 89.3 (child-reported) were achieved. Among the 32 parents, 24 expressed high satisfaction, 5 expressed moderate satisfaction, and 3 expressed fair satisfaction. Conclusion The early, progressive, and consistent use of an extension brace significantly improved joint mobility and corrected camptodactyly and clasped thumbs. It can be an effective approach to addressing hand deformities in patients with DA.